Mega tourism development projects in the Middle East - Ladki, Said (2012)
This paper reports about a proposed man made island off the coast of Lebanon. The advantages and disadvantages of island development are presented. Cedar Island is an $8.2 billion tourism development initiative designed to help Lebanon regain its pre 1975 tourism eminence. The island is still in its early planning phase and it has generated much controversy. Although this project promises several tourism, economic, and employment opportunities, environmentalists and community residents believe that the island initiative is a hoax; it is not well researched and developed, and may never materialize. If island developers were to integrate environmental, economic, social and cultural concerns into their revised planning phase, an all win situation could be achieved.